Everyday happy herbivore : over 175 quick-and-easy fat-free and low-fat vegan recipes - Nixon, Lindsay S. (Dallas, Tex. : BenBella Books, 2011)
"After vegan chef Lindsay S. Nixon wrapped up her popular cookbook The Happy Herbivore Cookbook last year, she went back to her kitchen in her new home of St. Maarten. Island living encouraged her to come up with simpler recipes, which led her to create a follow-up cookbook with a focus on recipes that bring tasty back to quick-and-easy. Now, in Nixon's much-anticipated follow-up cookbook, Everyday Happy Herbivore, readers will see, once again, that just because plant-based eating is optimal for health, that doesn't mean it has to be expensive or time-consuming. Everyday Happy Herbivore will include more than 175 doable recipes--recipes that are so quick and easy, you could cook three healthy meals from scratch every day. Each of Nixon's recipes are made with wholesome, easy-to-find, fresh ingredients and include no added fats. With additional notes indicating recipes that are ideal for preparing ahead of time and those you can whip up with just a few dollars, Everyday Happy Herbivore will be the must-have cookbook for anyone desiring a healthier, happier menu!"--
Includes index.
Keywords: Vegan cooking; Low-fat diet -- Recipes; COOKING / Vegetarian & Vegan